A Study of Dimensions of Islamophobia in Nigeria: Causes and Solutions - AbdulHameed Badmas Yusuf; Olalekan Rasheed Azeez (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Islamophobia is an unfounded fear of Islam and, more accurately, of his adherents i.e. Muslims. This phenomenon has found a fertile terrain in Nigeria given her status as a multi-religious society where Muslims and Christians live together as citizens. Over the years, Islamophobia has taken constitutional, diplomatic, educational, financial, and political dimensions in the country. Any Attempt by Muslims to live in line with their religious codes of conduct and without violating the constitutional provisions is often misconstrued by Christians - their religious counterparts- as a systematic way of Islamizing the country. However, the imaginary fear of Islam/Muslims by Christians is belied by the realities on ground. Against this backdrop, this paper will cast a look at Islamophobia as a concept with a view to highlight its various dimensions in Nigeria. After identifying possible causes of Islamophobia, practicable solutions shall be proffered accordingly. To achieve the objective, both historical and analytical methods shall be employed. Available resources as well as events in the recent past reveal that Islamophobia is not unconnected with misinformation about Islam at the instance of some orientalists. It is also a possible consequence of violent activities of insurgent groups like Boko Haram which proclaim the Islamization agenda to terrorize the entire nation. The paper shall show that this insurgent group is ignorance based and stands condemned by the Muslim authority in the country. As such, the paper suggests adequate knowledge and tolerance as critical tools to curtail the menace of Islamophobia. This will go a long way in achieving mutual tolerance and peaceful co-existence among the adherents of Christianity, Islam, and other religions in Nigeria.